PENGEMBANGAN MODUL AJAR BERDIFERENSIASI MATA PELAJARAN BAHASA INDONESIA KELAS II MATERI KALIMAT TANYA - Arissandy, Gaby Christya; Kurniastuti, Irine (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Students have a diversity of needs that are often not well accommodated by teachers. This study aims to develop and determine the quality of differentiated learning teaching modules for subjects Indonesian question sentence material for grade II students. The development of differentiated teaching modules is expected to assist teachers in compiling learning activities based on the diversity of students. This research was carried out at Mangunan Experimental Elementary School using ADDIE type Research and Development research. The teaching module developed contains the steps for making and examples of learning designs. This research was validated by three validators who then tested the module on a learning group of 26 grade 2 students with the results of the initial assessment having different learning readiness, interests and learning styles, and four students with special needs: autism, slow learners, speech delay, and ADHD. Based on the results of expert validation, the quality of teaching modules is stated to be very good judging from the module criteria, namely: containing essential material, fostering interest, challenging, relevant, providing learning based on the results of assessment of student needs, presenting variations in the learning process, content, products, and environment. The results of the trial at the first meeting, showed an increase in understanding by 73.90% in learning question sentences. Learners show enthusiasm and increased involvement in the learning process as their learning readiness, interests, and learning styles are accommodated. This research is limited to the trial of the first meeting of the teaching module and still requires trials for subsequent meetings for more comprehensive results